Peach - Glass, Emma. (London, England, UK : Bloomsbury Publishing, 2019)
Peach is a teenage girl like any other. She has college, and her friends, and her parents and the new baby, and her gorgeous boyfriend Green. She has her friend Sandy, and Sid the cat, and homework to do. But something has happened, something unspeakable and her world has become unfamiliar, fractured into strange textures and patterns. Reeling through her refracted universe, Peach knows that the people she loves are in danger, real danger. If she is not to be swallowed whole, Peach must summon all her courage and dig deep into something nameless and strange that lies within her.
GS
Text in English
Keywords: Women -- Violence against -- Fiction; Psychic trauma -- Fiction; Children's stories